Immunotolerant Properties of Mesenchymal Stem Cells: Updated Review - Whitney Faiella; Rony Atoui (Hindawi Limited, 2016)
Stem cell transplantation is a potential therapeutic option to regenerate damaged myocardium and restore function after infarct. Current research is focused on the use of allogeneic mesenchymal stem cells (MSCs) due to their unique immunomodulatory characteristics and ability to be harvested from young and healthy donors. Both animal and human studies support the immunoprivileged state of MSCs and even demonstrate improvements in cardiac function after transplantation. This research continues to be a topic of interest, as advances will ultimately enable the clinical use of these universal cells for therapy after a myocardial infarction. Updated in vitro, in vivo, and clinical trial studies are discussed in detail in the following review.